2020
DOI: 10.33865/ijcrt.002.01.0365
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drought stress on physiological properties of cotton (G. Hirsutum L.)

Abstract: As cotton is a product that is grown by irrigating during the summer and rainfall periods, global warming and the drought stress associated with it affect the cotton cultivation negatively. The aim of this study was to investigate the effects of different field capacity saturation degrees (FCSD) on some physiological properties of cotton cultivars. The study was carried out in Dicle University Faculty of Agriculture in the experimental area in 2014-2015 with 3 replications according to the split plot design. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This can be interpreted as a relationship with the plant roots extending their roots further and developing their roots more to access water in case of water deficiency in the soil. Ekinci and Basbag (2019) reported that the cotton plants growing in drought conditions showed more root development to reach soil water. However, in the opposite direction, Ahmadi et al (2018) found that root development of barley exposed to water stress decreased.…”
Section: Resultsmentioning
confidence: 99%
“…This can be interpreted as a relationship with the plant roots extending their roots further and developing their roots more to access water in case of water deficiency in the soil. Ekinci and Basbag (2019) reported that the cotton plants growing in drought conditions showed more root development to reach soil water. However, in the opposite direction, Ahmadi et al (2018) found that root development of barley exposed to water stress decreased.…”
Section: Resultsmentioning
confidence: 99%